Development of SITU: a survey to measure the impact of outreach activities. (1st July 2020) - Vardy, Emma; Upton, Penney; Upton, Dominic
The Office for Students' (OfS) aims are clear that it wants to increase robust evidence to understand the impact of outreach activities. There are different mechanisms to collate this evidence which outreach departments can use. To support the collection of robust evidence, this paper outlines the development of Students' Intentions towards University (SITU), a survey that practitioners can use as part of evaluating outreach activities such as ad hoc events or intensive interventions. This paper outlines the four stages that were undertaken to develop SITU to ensure a reliable and valid measure was constructed. At each stage, young people (aged 13 to 18) were consulted to ensure the measure was fit for purpose. The final survey comprises 15 items and is a quick, easy-to-administer survey that practitioners can use confidently. It is proposed that the survey will provide a valid data-collection tool to measure the outcome of outreach activities and the paper will be used as a guide for outreach departments to construct their own measures. Further research is required to test the application of the measure.